Problems faced by students of ODL System in North India States - Chaudhary, Dr. Neelam (IJRDO-Journal of Applied Science, 2018)
This research study was conducted to find the problems faced by students ofOpen & Distance Learning System at their Graduate Level Study in NorthIndian States. The students living in remote and rural areas are already at thecorner and are not having group discussions, any kind of debate related withtheir study in ODL system. What are their main problematic areas and where weshould focus, here we tried to find out.